Pollution, sources, and risks of heavy metals in coastal waters of China. Issue 8 (13th September 2020) - Wu, Jun; Lu, Jian; Zhang, Cui; Zhang, Yuxuan; Lin, Yichen; Xu, Juan
Abstract: Comprehensive information on heavy metals in coastal waters at national scale of China is limited. Therefore, this study investigated the distribution, pollution, and ecological-health risks of heavy metals in coastal waters along 18, 000 km coastline of China. Total 13 target heavy metals in coastal waters along coastline of China showed drastic spatial variations with average concentrations ranging from .14 (Cd) to 136.26 (Cu) μg/L. Cu was the dominant heavy metal with the maximal concentration of 1485.92 μg/L. Three methods including heavy metal pollution index ( HPI ), Nemerow index ( NI ), and contamination degree ( CD ) were adopted to explore heavy metal pollution. HPI obtained the worst-case evaluation results to illustrate that heavy pollution occurred at over 50% of sampling sites. Anthropogenic sources were the main sources of heavy metals in the coastal waters. Approximately 28.13% and 9.38% of sampling sites illustrated considerable and very high ecological risks, respectively. Metals including Cu, As, and Hg were the main pollution and risk contributors. Heavy metals in coastal waters posed high cancer risks and unacceptable non-cancer risks to both adults and children. Therefore, effective control of heavy metals is necessary for regional sustainability and well-beings of residents in coastal regions of China.